2011 Review of Conditionality and the Design of Fund-Supported Programs : Concept Note. (Policy Papers; Policy Paper ;, 2011)
The Fund regularly assesses conditionality in IMF-supported programs, with the next formal review planned for 2011. This paper summarizes previous assessments of conditionality, outlines staff's proposed approach to the forthcoming review, and seeks Directors' early views on the approach.